2000
DOI: 10.2337/diabetes.49.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antecedent hypoglycemia on subsequent counterregulatory responses to exercise.

Abstract: Antecedent hypoglycemia can blunt counterregulatory responses to subsequent hypoglycemia. It is uncertain, however, if prior hypoglycemia can blunt counterregulatory responses to other physiologic stresses. The aim of this study, therefore, was to determine whether antecedent hypoglycemia attenuates subsequent neuroendocrine and metabolic responses to exercise. Sixteen lean, healthy adults (eight men and eight women, ages 28+/-2 years, BMI 22+/-1 kg/m2, VO2max 43+/-3 ml x kg(-1) x min(-1)) were studied during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 26 publications
8
56
0
2
Order By: Relevance
“…In one study of type 1 diabetic subjects, the epinephrine and norepinephrine responses to exercise and upright posture were intact after antecedent hypoglycemia (19). Other studies of type 1 diabetic subjects suggested that the deficit is more generalized (20,21); the epinephrine and norepinephrine responses to a cold pressor test were reduced in wellcontrolled type 1 diabetic subjects (20), and antecedent hypoglycemia reduced the normal exercise-induced rise in epinephrine, norepinephrine, glucagon, growth hormone, pancreatic polypeptide, and cortisol in healthy individuals (21). Our data are consistent with these latter studies and strongly support the view that the effects of antecedent hypoglycemia on the autonomic nervous system are more generalized and not specific to subsequent hypoglycemic stimuli.…”
Section: Gk Adler and Associatesmentioning
confidence: 99%
“…In one study of type 1 diabetic subjects, the epinephrine and norepinephrine responses to exercise and upright posture were intact after antecedent hypoglycemia (19). Other studies of type 1 diabetic subjects suggested that the deficit is more generalized (20,21); the epinephrine and norepinephrine responses to a cold pressor test were reduced in wellcontrolled type 1 diabetic subjects (20), and antecedent hypoglycemia reduced the normal exercise-induced rise in epinephrine, norepinephrine, glucagon, growth hormone, pancreatic polypeptide, and cortisol in healthy individuals (21). Our data are consistent with these latter studies and strongly support the view that the effects of antecedent hypoglycemia on the autonomic nervous system are more generalized and not specific to subsequent hypoglycemic stimuli.…”
Section: Gk Adler and Associatesmentioning
confidence: 99%
“…While the role of IL-6 and other pro-and anti-inflammatory cytokines in the evolution of diabetes is still incompletely defined, the above evidence suggests that the simultaneous presence of diabetes, hyperglycemia, and intense exercise (all independently able to increase IL-6) may result in inappropriately elevated IL-6 concentrations, with potentially negative implications on the onset and progression of diabetic complications. It is also likely that hyperglycemia need not occur simultaneously with exercise to affect exercise-induced IL-6 secretion, as numerous exercise responses can be altered by prior, rather than concurrent, glycemic fluctuations (8,16).…”
mentioning
confidence: 99%
“…Essa queda na concentração de glicose também foi observada em outros modelos de exercício com duração superior a 90 minutos (44,45) . Provavelmente, a redução da glicemia foi decorrente do aumento da demanda imposta pelo músculo esquelético e/ou menor liberação/produção hepática de glicose (via glicogenólise e gliconeogênese).…”
Section: Suplementação De Carboidrato No Tênisunclassified